Implementasi Market Basket Analysis Menggunakan Assocation Rule Menerapkan Algoritma FP-Growth - Desi Asima Silitonga; Agus Perdana Windarto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Pharmacy is a medium for selling various kinds of drugs by class and other products related to health. Pharmacies serve transactions in the form of doctor's prescriptions and over-the-counter drugs every day. Drug sales per day can reach dozens of transactions. Sales transaction data in the form of doctor's prescriptions are increasing every day and are stored as archives for bookkeeping without thinking about other benefits. However, this data can produce important information in determining the pattern of goods layout in accordance with consumer buying patterns using the fp-growth algorithm. The data used in this study is based on doctor's prescription transaction data. The results of the association rule can be used as input for the pharmacy in determining the pattern of the location of the goods at the pharmacy